Stakeholder Collaboration in Traffic Accident Management - Dorisman, Asri; Suradji Muhammad, Adji; Setiawan, Ramadhani (Jurnal Magister Administrasi Publik, 2021)
This research aims to determine how the collaboration process between stakeholders in response to traffic accidents in Kota Tanjungpinang. In Kota Tanjungpinang accident numbers are still quite high from year to year. In response to traffic accidents in Kota Tanjungpinang some stakeholders such as Polres Tanjungpinang, Dinas Perhubungan Kota Tanjungpinang, PT. Jasa Raharja (Persero) Perwakilan Tanjungpinang, Dinas Pekerjaan Umum dan Penataan Ruang Kota Tanjungpinang, Dinas Perumahan Rakyat, Kawasan Permukiman, Kebersihan dan Pertamanan Kota Tanjungpinang collaborate. Data collection methods in the form of interviews that are conducted to the informant interested in the implementation of Collaborative governance process. The analysis of data obtained is carried out through data collection, data verification, data presentation, and withdrawal of conclusions. The results obtained from this research are Collaborative governance in response to this traffic accident has fulfilled several factors of 5 factors in collaboration according to the Ansell and Gash Theory (2007), a factor that is fulfilled by collaboration This is (1). Comitment to process in the collaboration of countermeasures traffic accidents see the commitment of each stakeholder and confidence in providing the best service for the countermeasures of traffic accidents. (2). The Trust building in the collaboration in response to the trust building traffic accidents between stakeholders has already run well in carrying out their roles.